PUBLIC EXTERNAL DEBT MANAGEMENT IN DEVELOPING COUNTRIES (Ustozlar uchun, 2024)
Public external debt, defined as the total amount owed by a government to foreign creditors, plays a significant role in shaping the economic landscape of developing countries. While external borrowing can finance infrastructure projects, stimulate growth, and address short-term financing needs, it also poses considerable challenges in terms of repayment obligations and vulnerability to external shocks. Effective management of public external debt is therefore crucial for achieving sustainable economic development and avoiding debt crises.